Direct Access to S-Heterocycles by Scandium(III) Triflate Catalyzed Cyclization of Aromatic Thiols and Diols - Minakawa, Maki; Minami, Keisuke; Sato, Yuya (Synlett, 2021)
A simple and environmentally friendly method to prepare S-heterocycles by cyclization of aromatic thiols and diols with H2O as a byproduct is described. The Sc(OTf)3-catalyzed dehydrative cyclizations of aromatic thiols and diols provided the corresponding thiopyran and thiophene derivatives. Control experiments were also performed to obtain insights into the reaction pathway
Keywords: S-heterocycles; diols; thiols; scandium triflate; cyclization; C–S bond formation